Perceived Behavioral Control merupakan Faktor Dominan yang Mempengaruhi Minat Menggunakan Layanan Medical Check Up - Chandoko, Citra (Jurnal Aplikasi Manajemen, 2013)
This study aimed to know which factor that mostly influenced intention of using Adi HusadaUndaan Wetan Hospital's own medical check up services. The study design was observational analiticsurvey using cross sectional study. The respondents were 64 outpatient visitors. Sampling method usedpurposive sampling. Data was analyzed by using multiple linier regression analysis. The study resultsindicated that the biggest antecedent contribution to the intention was given by perceived behavioralcontrol among attitude and subjective norm.